The perception of the UiTM percussion ensemble towards the sound & rhythm of ‘ionization’ by Edgard Varese / Heidi Vanessa Moruning - Moruning, Heidi Vanessa (Faculty of Music, 2017)
This research study consists of the UiTM Percussion Ensemble's own perception in understanding the sound and rhythm in performing the Ionisation by Edgard Varese. It is interesting to understand and explore on each percussion player gets to understand what the piece really is about in terms of rhythmic patterns, instrumentation. They are also given different types of percussive instruments, and each player is required to have a minimum of two percussive instruments. In this study, I will also explain the analysis of the score Ionisation whereby it will make deeper understanding in terms of sound and rhythm of the composers intention. My analysis covers the, instrumentation of the piece as well as tempo, the rhythmic patterns as well as the rapid changes of time signature involved in the piece.